The Mistaken Implementation of the Destination Principle to the Value-Added Tax Collection Partners of State-Owned Enterprises (The Study of Case Number 1263/PID.SUS/2019/PN.JKT.PST and 678/PK/PID.SUS/2023) - Purnomo, Chessa Ario Jani (Journal of Legal and Cultural Analytics, 2024)
MAS's first instance decisions in sentenced him to prison and fined him for violating Article 39 paragraph (1) letter i of Law Number 16 of 2009 and acknowledged his VAT debt settlement. At the judicial review level, the criminal fine of 3 times the VAT owed was not proportional (double jeopardy) and the VAT was overpaid, and the Prosecutor was ordered to return it to the defendant MAS, but the person was still criminally guilty. Additionally, the value-added tax law extends the destination principle to state-owned firms. The analysis shows that the defendant MAS's actions constitute administrative tax acts due to the broadening of the destination principle in Article 16A of Law Number 42 of 2009.